Health endowment and later-life outcomes in the labour market: Evidence using genetic risk scores and reduced-form models - Jaakko Pehkonen; Jutta Viinikainen; Petri Böckerman; Niina Pitkänen; Terho Lehtimäki; Olli Raitakari (Elsevier, 2019)
This paper examines the relationship between health endowment and later-life outcomes in the labour market. The analysis is based on reduced-form models in which labour market outcomes are regressed on genetic variants related to the increased risk of cardiovascular diseases. We use linked Finnish data that have many strengths. Genetic risk scores constitute exogenous measures for health endowment, and accurate administrative tax records on earnings, employment and social income transfers provide a comprehensive account of an individual's long-term performance in the labour market. The results show that although the direction of an effect is generally consistent with theoretical reasoning, the effects of health endowment on outcomes are statistically weak, and the hypothesis of no effect can be rejected only in one case: genetic endowment related to obesity influences male earnings and employment in prime age. Due to the sample size (N = 1651), the results should be interpreted with caution and should be confirmed in larger samples and in other institutional settings. JEL classification: D62, I1, I12, J01, J24, J3, J7, Keywords: Genetics, Health endowment, Earnings, Employment, Social income transfers, Reduced-form regression